Personal protection and influencing factors of livestock workers in Xinjiang - Xixiao MA; Xueying XIANG; Zhaojie WANG; Wanting XU; Jiguo JIN; Fan WU; Xiangnan WEI; Jianyong WU; Fuye LI (环境与职业医学)
BackgroundPersonal protection is crucial for reducing the risk of zoonotic pathogen infection among livestock workers. Investigating the current status of its implementation and associated influencing factors can provide empirical evidence for developing more effective intervention measures. ObjectiveTo investigate the current status of personal protection implementation among livestock workers in Xinjiang, China and its influencing factors, providing a reference for formulating targeted intervention measures. MethodsThis study was conducted in Bayingolin Mongol Autonomous Prefecture, Kashgar region, and the First and Eighth Divisions of Xinjiang Production and Construction Corps. We selected large-scale cattle and sheep farms, cooperatives, individual livestock households, livestock trading markets, slaughterhouses, and retail markets. Using cluster sampling, we recruited all livestock workers (1074 participants) at sampled sites. During the period from April to July 2024, we conducted face-to-face surveys with a self-designed questionnaire among livestock workers, collecting general demographic information, occupational exposure history, and information related to the use of personal protective equipment, resulting in 939 valid questionnaires. EpiData 3.1 was used for data entry and SPSS 26.0 for statistical analysis. We employed logistic regression to compare the implementation of personal protection among workers by selected categories. ResultsAmong the study subjects, there were 300 workers from large-scale farms (31.95%) and 583 self-employed livestock farmers (62.09%). The sample included 600 males (63.90%) and 339 females (36.10%). The majority of the study subjects was farmers, breeders, or aged 18-60 years (87.75%), auxiliary workers (87.97%) and had an education level of junior high school or below (81.36%). The proportion of workers who consistently and correctly implemented all five personal protective measures (washing hands after work, wearing gloves, wearing masks, wearing dedicated work clothes, and using rubber boots) was 35.14% (330/939). The implementation rates for these five protective measures were 93.61% (879/939), 58.68% (551/939), 57.93% (544/939), 46.01% (432/939), and 42.81% (402/939), respectively. There were statistically significant differences in the implementation rates of differen personal protective measures among the workers by occupation and education level (P<0.05). Among them, workers with lower education levels had lower implementation rates for various protective measures. The results of logistic regression indicated that, compared to male workers, female workers (OR=2.26, 95%CI: 1.68, 3.04) showed a higher rate of non-standard implementation of personal protection. Using the age group of 18 to less than 36 years as a reference, those aged 36 to less than 60 years (OR=1.82, 95%CI: 1.33, 2.50) and 60 years or older (OR=4.45, 95%CI: 2.56, 7.73) reported higher rates of non-standard implementation of personal protection. Compared to those with an education level of primary school or below, those with a junior high school education (OR=0.64, 95%CI: 0.47, 0.88) and a high school education or above (OR=0.13, 95%CI: 0.19, 0.29) showed lower rates of non-standard implementation of personal protection. Compared to farmers, veterinarians (OR=0.03, 95%CI: 0.02, 0.07) reported the lowest rate of non-standard implementation of personal protection, followed by auxiliary workers (OR=0.08, 95%CI: 0.05, 0.12), breeders (OR=0.10, 95%CI: 0.07, 0.15), and other occupational groups (OR=0.28, 95%CI: 0.15, 0.52). Using large-scale farms as a reference, self-employed farmers (OR=13.5, 95%CI: 9.65, 18.88) reported a higher rate of non-standard implementation of personal protection, followed by workers from other workplaces (OR=3.63, 95%CI: 2.01, 6.54). ConclusionThe implementation of personal protective measures among livestock workers in Xinjiang is generally satisfactory. However, significant disparities in the execution of these measures exist among different types of workers, indicating the need to enhance occupational health promotion to reduce the risk of zoonotic pathogen infection among the workers.